Metagenomic Insights Into the Effects of Rare-Earth Elements Supplementation on Rumen Digestibility and Meat Quality of Beef Cattle - Xu, Lanjiao; Wen, Luhua; Ge, Yu; Wan, Gen; Qu, Mingren; Xue, Fuguang (Frontiers in Microbiology, 2020)
Rare-earth elements (REE), supplemented as feed additives, effectively improved feed conversion and production performances of monogastrics. However, very little information exists on how REE supplementation affects ruminants. In the present study, twenty-four 18-month-old Jinjiang bull cattle, with initial body weight (BW) of 374.75±14.02 kg, were randomly allotted into four dietary treatments with a 15-day-long preliminary trial: a control treatment (basal diet), a 400 mg/kg REE treatment (basal diet supplemented with 400mg REE/kg DMI), an 800 mg/kg REE treatment (basal diet supplemented with 800mg REE/kg DMI), and a 1200 mg/kg REE treatment (basal diet supplemented with 1200mg REE/kg DMI). Based on the results, the optimum supplementation scale was chosen for a 60-day-long follow-up feeding procedure. At the end of the feeding period, all bull cattle were slaughtered. Feed intake, average daily weight gain, carcass performances, meat quality, and rumen microbiota were measured. Results indicate a positive responses of growth performance and gastrointestinal digestibility to REE supplementation, and 400mg/kg DMI treatment presented the most average daily feed intake (ADFI), the best average daily weight gain (ADG), and the least F/G. REE also significantly decreased the ruminal propionate content compared with control treatment. As to the aspect of microbiota, despite no increases in the bacterial community abundance, the proliferation of Bacteroidetes and Tenericutes while suppression of Actinobacteria was found under REE treatment. Furthermore, REE treatment significantly increased the meat protein content and decreased meat fat content. Likewise, activities of the enzymes related to lipid synthesis. such as fatty acid synthetase (FAS) and malate dehydrogenase (MDH), were significantly suppressed, while the activity of lipolysis-related enzyme, lipoproteinesterase (LPL), was enhanced. In summary, REE supplementation provided an effective regulation on ruminal microbiota, facilitation on ruminal fiber digestibility, promotion on feed conversion, suppression on lipid deposition, and finally improved the production and meat quality of beef cattle.